Association of ADAMTS4 and ADAMTS9 levels with cardiovascular risk in patients with primary hyperparathyroidism. (2nd January 2018) - Karakose, Melia; Caliskan, Mustafa; Arslan, Muyesser Sayki; Demirci, Taner; Karakose, Suleyman; Tutal, Esra; Cakal, Erman
ABSTRACT: Purpose : Primary hyperparathyroidism (PHPT) has been associated with increased incidence of morbidity and mortality of the cardiovascular system. The pathogenetic mechanisms underlying this association are still not completely clear. A disintegrin and metalloproteinase with thrombospondin-like motifs (ADAMTS) play a critical role in atherosclerosis. This study aimed to investigate the levels of ADAMTS4 and ADAMTS9 and relationship between these proteoglycanases and cardiometabolic abnormalities in PHPT.Materials and Methods : A case-control study was performed in a training and research hospital. Fifty-six patients with PHPT and 61 healthy volunteers were recruited. The Framingham score was used to calculate cardiovascular risk (CVR). Serum ADAMTS levels were determined by a human enzyme-linked immunoassay in all subjects. Results : The ADAMTS9 concentration was significantly higher in patients with PHPT than in the control group ( p  < 0.05); however, there were no significant differences in ADAMTS4 levels between the groups ( p  > 0.05). In ROC curve analysis, PHPT can be predicted by the use of ADAMTS9 at a cut-off value of 30.7 pg/mL (69% sensitivity, 65% specificity). CVR score was significantly increased in the PHPT than controls ( p  < 0.05). ADAMTS4 and ADAMTS9 levels had positive correlations with CVR score (r = 0.322, p  = 0.017; r = 0.275, p  = 0.044 respectively).Conclusions : Based on the results of the present study, cardiovascular risk is increased in PHPT and associated with ADAMTS4 and ADAMTS9. Further efforts are needed to establish the function of ADAMTS proteases in both PHPT and atherosclerosis.